Fentanyl decreases arterial blood oxygen saturation more than furanylfentanyl in mice due to increased apnea - Catherine Demery; Sierra C. Moore; Kelsey E. Kochan; Mengchu Li; Thomas D. Prince; Benjamin M. Clements; Zhongqi Chen; Jessica R. Whitaker-Fornek; Erica S. Levitt; Jessica P. Anand; John R. Traynor (Psychopharmacology, 2026)
Rationale Fatal opioid overdoses involving synthetic opioids have increased >10-fold over the past 8 years. Fentanyl, a potent synthetic opioid acting at the mu-opioid receptor (MOR), has largely replaced heroin as the predominant illicit opioid available. Various analogs have been synthesized from the fentanyl scaffold, including 2-furanylfentanyl, one of the most trafficked analogs from 2019 to 2024. Despite its prevalence, the in vivo effects of furanylfentanyl are not well characterized, especially regarding respiratory depression. Objectives To characterize furanylfentanyl relative to fentanyl in vitro and compare the effects of both drugs in mouse models of antinociception and respiratory depression. Methods The affinity and potency of fentanyl and furanylfentanyl were determined in CHO cells overexpressing MOR. Male and female CD-1 mice were administered ( i.p. ) fentanyl or furanylfentanyl prior to measuring antinociception (warm-water tail withdrawal), respiration (whole-body plethysmography), or oxygen saturation (pulse oximetry). Results Furanylfentanyl behaves as a partial agonist in vitro relative to fentanyl and morphine but with similar affinity and potency at MOR. In mice, fentanyl and furanylfentanyl produced similar effects on breathing parameters (including rate and inspiration time) that were greater than those induced by morphine, yet only fentanyl caused a drastic, long-lasting depletion of blood oxygen saturation. The discrepancy between effects on breathing and oxygen saturation may be explained by a greater number of apneas induced by fentanyl. Conclusions These results highlight the complexity of fentanyl-induced respiratory depression and indicate that recreational use of 2-furanylfentanyl in humans may pose a greater risk of overdose than morphine but lesser than fentanyl.

Exploring new antecedent metrics for safety performance in Ghana’s oil and gas industry using partial least squares structural equation modelling (PLS-SEM) - Elvis Kwame Ofori; Simon Appah Aram; Benjamin M. Saalidong; Justice Gyimah; Patrick Niyonzima; Clement Mintah; Isaac Ahakwa (Resources Policy, 2023)

Paternally‐biased gene expression follows kin‐selected predictions in female honey bee embryos - Nicholas M. A. Smith; Boris Yagound; Emily J. Remnant; Charles S. P. Foster; Gabriele Buchmann; Michael H. Allsopp; Clement F. Kent; Amro Zayed; Stephen A. Rose; Kitty Lo; Alyson Ashe; Brock A. Harpur; et al. (Molecular Ecology, 2020)
The Kinship Theory of Genomic Imprinting (KTGI) posits that, in species where females mate with multiple males, there is selection for a male to enhance the reproductive success of his offspring at the expense of other males and his mating partner. Reciprocal crosses between honey bee subspecies show parent‐of‐origin effects for reproductive traits, suggesting that males modify the expression of genes related to female function in their female offspring. This effect is likely to be greater in the Cape honey bee ( Apis mellifera capensis ), because a male's daughters have the unique ability to produce female offspring that can develop into reproductive workers or the next queen without mating. We generated reciprocal crosses between Capensis and another subspecies and used RNA‐seq to identify transcripts that are over‐ or underexpressed in the embryos, depending on the parental origin of the gene. As predicted, 21 genes showed expression bias towards the Capensis father's allele in colonies with a Capensis father, with no such bias in the reciprocal cross. A further six genes showed a consistent bias towards expression of the father's allele across all eight colonies examined, regardless of the direction of the cross. Consistent with predictions of the KTGI, six of the 21 genes are associated with female reproduction. No gene consistently showed overexpression of the maternal allele .

A bioenergetic framework for the temperature dependence of trophic interactions - Benjamin Gilbert; Tyler D. Tunney; Kevin S. McCann; John P. DeLong; David A. Vasseur; Van Savage; Jonathan B. Shurin; Anthony I. Dell; Brandon T. Barton; Christopher D.G. Harley; Heather M. Kharouba; Pavel Kratina; et al. (Ecology Letters, 2014)
Changing temperature can substantially shift ecological communities by altering the strength and stability of trophic interactions. Because many ecological rates are constrained by temperature, new approaches are required to understand how simultaneous changes in multiple rates alter the relative performance of species and their trophic interactions. We develop an energetic approach to identify the relationship between biomass fluxes and standing biomass across trophic levels. Our approach links ecological rates and trophic dynamics to measure temperature‐dependent changes to the strength of trophic interactions and determine how these changes alter food web stability. It accomplishes this by using biomass as a common energetic currency and isolating three temperature‐dependent processes that are common to all consumer–resource interactions: biomass accumulation of the resource, resource consumption and consumer mortality. Using this framework, we clarify when and how temperature alters consumer to resource biomass ratios, equilibrium resilience, consumer variability, extinction risk and transient vs. equilibrium dynamics. Finally, we characterise key asymmetries in species responses to temperature that produce these distinct dynamic behaviours and identify when they are likely to emerge. Overall, our framework provides a mechanistic and more unified understanding of the temperature dependence of trophic dynamics in terms of ecological rates, biomass ratios and stability.